Provas algébricas: uma investigação sobre as justificativas de alunos da educação básica - Ferreira, Luiz Donizeti (2008)
This assignment has the objective to investigate the students test culture from regular education, mainly from 8th grade and 1st year from Junior High School on Algebra subject. The assignment is part of the Approve Me Project (Argumentation and Mathematic Test) developed on biennium basis 2005-2007, has the objective to measure the argumentation process and to test teenagers from public and private schools from São Paulo State. The referred assignment was done through a questionnaire composed by 5 questions of Geometry and 5 of Algebra, applied to 1998 teenagers from ages 14 to 16. After counting the 1998 student s data, we extracted a sample of 50 individuals, aiming the detailed analysis of its answers and justification presented to one of the algebra member. Our analysis examined the answers and justifications to these questions. We used the statistics and multidimensional software CHIC to analyze the data. Our conclusions point out the below average performance, as only 20,5% of the students from our group of sample presented correct justifications to the investigated questions, being predominant the use of the natural language, none of the students used a formal language on their justified answers. We detach the preference for the use of the calculation in the justifications in detriment of the use of the properties We also emphasize that the students from the 8th grade had better performance than Junior High School